National trends in treatments for ectopic pregnancy in Japan from 2010 to 2020: a retrospective observational study - Risa Ishida; Hiroyuki Ohbe; Gentaro Izumi; Daisuke Shigemi; Hiroki Matsui; Kaori Koga; Hideo Yasunaga; Yutaka Osuga (Journal of Obstetrics and Gynaecology)
Background Ectopic pregnancy (EP) can be treated surgically or nonsurgically. In many countries, methotrexate is frequently used as a first-line medical treatment, and its effect is similar to that of surgery in selected patients. We aimed to investigate national trends in the treatment of EP in Japan.Methods We conducted a retrospective observational analysis between 2010 and 2020 using a nationwide claims database that included inpatient data. We identified female inpatients with EP aged 15 to 49 years old. We analysed year-to-year treatment trends for EP, as well as year-to-year trends in methotrexate administration, with a focus on the site of the pregnancy. Patients who received methotrexate were divided into two groups: Those with and those without surgery after methotrexate use. We compared the characteristics of these groups and calculated the methotrexate success rate.Results We identified 53,653 patients with EP. The proportion of patients undergoing surgery increased from 79% in 2010 to 83% in 2020, whereas the proportion of methotrexate therapy decreased from 8.1% in 2010 to 5.1% in 2020. Regarding methotrexate use for the site of the pregnancy, there was a significant downward trend in methotrexate therapy for tubal pregnancies. Notably, the methotrexate success rate was 84% during the study period.Conclusions Surgery showed an increasing tendency over time, whereas methotrexate therapy showed a decreasing tendency for EP treatment in Japan. The efficacy of methotrexate in Japan was comparable to that observed in other countries.